THE ROLE OF CURRICULUM MANAGEMENT IN IMPROVING STUDENT LEARNING OUTCOMES IN PRIMARY SCHOOLS - Rahmatul Ukhra; Irda Rafika; Suci Rahmi Amjusfa (Journal Informatic, Education and Management (JIEM), 2026)
Education has an important role in shaping the nation’s civilization , and Curriculum as one of the core components in the education system plays a strategic role in the achievement of national education goals . This research aims to analyze curriculum management in primary schools , which includes planning, implementation, and evaluation, as well as its implications for student learning outcomes . The method used in this research is literature research , by studying literature related to relevant topics . Research results show that mature curriculum planning , well -organized implementation , and effective evaluation can improve the quality of education, which in turn improves student academic performance . In addition , effective curriculum management also affects the development of student character . The implication of this research is the importance of synergy between the relevant parties in education, including teachers, principals , parents , and the community, to create an educational environment that is conducive and supports success.